NMR approach to characterize Bcl-xl structure and interaction mechanism in membrane state - Liu, Wei (2014)
Bcl-2 family proteins play central roles in the apoptotic regulation at the mitochondrial membrane. Bcl-XL belongs to the anti-apoptotic subfamily of the Bcl-2 family. It interacts with pro-apoptotic subfamilies to inhibit them from forming pores on the mitochondrial membrane. Our current understanding on the function of Bcl-XL is primarily based upon its structural features and molecular characteristics in solution. Currently the membrane structure of Bcl-XL and its molecular mechanism in membrane environment remain poorly understood. Understanding the mode of binding is essential to unravel the biological function of proteins. In this thesis research we have characterized Bcl-XL in a detergent micelle which mimics membrane environment by employing biophysical methods including NMR spectroscopy. We first assigned NMR resonances of Bcl-XL and determined structure of Bcl-XL in DPC micelle. Furthermore, the binding mechanism with other Bcl-2 family members was also examined in detergent micelle by employing NMR spectroscopy. The molecular binding analysis demonstrated that the BH3 peptides fail to bind with Bcl-XL in micelle, indicating that Bcl-XL undergoes structural transition when Bcl-XL anchors to the micelle. Even though truncated Bid maintains the binding ability to Bcl-XL in micelle, NMR cross-saturation data indicates that the binding interface is significant different from that in solution phase. Based on the results, we proposed an interaction model of Bcl-XL in apoptosis regulation.